The Use of Story Pyramid Strategy to Improve Reading Comprehension of the Students in SMP 2 Sungguminasa - Muh. Djakkir; Syarifuddin Dollah; Ahmad Talib (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study is the pre-test and post-test that aimed to know the effect of using the story pyramid strategy to improve reading comprehension. The research design was pre-experimental. The population of this research was the Eighth-Grade students of SMPN 2 Sungguminasa, and the total population was 28 students. The sample of this research was class VIII. The research instrument was a reading test consisting of 15 items in the form of multiple choices. The technique of data analysis used a purposive sampling technique. Based on the results of the study, it is known that the posttest mean score (78.75) is greater than the pre-test means score (42.86). The result is that T-count (20.346) is greater than the t-table (2.064). This means that H0 is rejected and H1 is accepted. It is concluded that there was an effect of using story pyramid strategy to improve reading comprehension of the students in SMP 2 Sungguminasa.